Governance of Village Boundary Segment Affirmation: A Qualitative Study of Sea and East Koha Villages in Minahasa Regency - Villy F. Setiono; Devie S. R. Siwij; Laurens L. Bulo (JR Education, 2026)
This article analyzes the governance of village boundary segment affirmation between Sea Village and East Koha Village in Minahasa Regency. The study is situated within public administration, public management, territorial administration, and boundary governance. The case is important because village boundaries are not merely cartographic lines; they define administrative authority, public service jurisdiction, planning responsibility, asset management, and community access to government protection. Although formal procedures for village boundary determination and affirmation are provided by the Indonesian regulatory framework, the boundary segment between the two villages has not reached a final agreement. This article uses a qualitative descriptive approach based on in-depth interviews, document analysis, and limited administrative observation. The findings show that the boundary affirmation process has already passed several formal stages, including team formation, data and document collection, facilitation, cartometric tracing, and preparation of maps and coordinates. Nevertheless, the process remains unresolved because socio-historical interpretations, institutional governance limitations, inter-actor coordination, local leadership dynamics, and the low level of social pressure have prevented the transformation of technical outputs into a binding administrative decision. The study concludes that unresolved village boundary affirmation is less a purely technical mapping problem than a governance problem that requires stronger coordination, shared interpretation of evidence, community legitimacy, and decisive administrative follow-up. The article recommends an integrated boundary governance model that combines legal certainty, geospatial evidence, participatory mediation, and final decision-making by authorized local government institutions.